The effect of organisational ethical climate and peer monitoring control systems on budgetary slack: an experimental study / Vincent K Chong and Danny Sudarso - K Chong, Vincent; Sudarso, Danny (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2016)
This study addresses the following research questions. Firstly, does a peer monitoring control system provide an ideal opportunity for managers to build slack into their budgets in team-based settings? Secondly, does the organisational ethical climate influence the propensity of managers to create budgetary slack? Lastly, what is the effect of peer monitoring control systems and organisational ethical climate on budgetary slack creation by managers? A laboratory experiment was conducted. Results indicate that a peer monitoring control system provides an ideal opportunity for managers to build slack into their budgets. The organisational ethical climate can influence the ethical behaviours of subordinates. Under a weak organisational ethical climate, subordinates are likely to engage in opportunistic behaviour. Furthermore, budgetary slack creation is low in the absence of a peer monitoring control system and a strong organisational ethical climate exists.